Occurrence and risk factors of Vitamin D deficiency in Indian children living with HIV – A case–control study - Garg, Shikha; Hemal, Alok; Goyal, Parul; Arora, Shilpa Khanna (Indian Journal of Child Health, 2020)
Background: Vitamin D deficiency (VDD) is highly prevalent in healthy individuals. Studies suggest that Vitamin D plays an important role in immune system. Objective: The objective of this study was to assess the frequency of VDD in Indian children living with HIV (CLHIV) and to find out the risk factors associated with it. Materials and Methods: It was a cross-sectional comparative study conducted in a tertiary care teaching hospital of North India. A total of 52 CLHIV were enrolled consecutively from the pediatric HIV center and an equal number of age- and sex-matched controls were enrolled from the pediatric outpatient department. Serum Vitamin D levels of cases and controls were assessed and compared. Various risk factors, both classical (age, sex, sunlight exposure, average dietary intake of calcium, and Vitamin D) and disease related (WHO and immunological stage, duration, and regimen of treatment), were evaluated for VDD in CLHIV. Results: The prevalence of VDD in cases and controls was 69.23% and 19.23%, respectively (p<0.001). The mean serum Vitamin D level of the cases (18.24±11.2 ng/dL) was significantly lower than that of controls (31.58±17.31 ng/dL) (p<0.001). The risk factor that predicted the occurrence VDD in CLHIV was a poor intake of Vitamin D. Conclusion: CLHIV are more prone to VDD; hence, there is a need to regularly evaluate, supplement, and monitor for Vitamin D status in these children.